FACTORS AFFECTING ACCOUNTING LEARNING ACHIEVEMENT - Brilia Afnizar Litasari; Adeng Pustikaningsih (Jurnal Pendidikan Akuntansi Indonesia, 2018)
This study aimed to know the influence of (1) Locus of Control (2) Student Perceptions of Teaching Methods (3) The Use of Learning Resources, and (4) Locus of Control, Student Perceptions of Teaching Methods, and The Use of Learning Resources simultaneously toward Accounting Learning Achievement Students Class of X, XI, XII Accounting SMK Muhammadiyah 2 Moyudan Academic Year 2017/2018. Data collection technique used in this research was questionnaire and documentation. Population of this research was students of class X, XI, and XII Accounting SMK Muhammadiyah 2 Moyudan. The research showed that there is a (1) positive and significant influence of Locus of Control toward Accounting Learning Achievement 2) positive and significant influence of Student Perceptions of Teaching Methods toward Accounting Learning Achievement (3) positive and significant influence of The Use of Learning Resources toward Accounting Learning Achievement (4) positive and significant influence of Locus of Control, Student Perceptions of Teaching Methods, and The Use of Learning Resources  simultaneously toward Accounting Learning Achievement. Keywords: Accounting Learning Achievement, Locus of Control, Student Perceptions of Teaching Methods, The Use of Learning Resources